Differential impact of the school context on ethnic and racial identity and depression for monoracial and multiracial early adolescents - Huang, Cindy Y.; Hunt, Emily; Stormshak, Elizabeth A. (Frontiers in Psychiatry, 2023)
This study examined the direct and indirect effects of school context (negative peer relationships, school environment) on ethnic and racial identity (ERI) development in middle school and later depression symptoms in high school. Differences by racial group were examined for non-Hispanic White (NHW) early adolescents, monoracial adolescents, and multiracial adolescents. This study used existing data from a large, multiwave, longitudinal study that included 593 racial/ethnically diverse adolescents from sixth grade through ninth grade across three public middle schools in the Pacific Northwest. Using multigroup path analysis in structural equation modeling, the findings indicated differences by racial group – school environment was associated with positive ERI development in middle school for NHW and monoracial adolescents but not for multiracial adolescents. For multiracial adolescents, ERI predicted later depression symptoms. These findings demonstrated the importance of examining school context and peer relationships in relation to ERI development and psychological well-being.